Typologies of internationally mobile employees - Andersen, Maike; Dickmann, Michael; Suutari, Vesa (Palgrave Macmillan, Cham, 2018)
When counting the number of internationally mobile employees (IMEs) and analyzing the consequences of international mobility in order to improve the management of different kinds of IMEs, who counts as an expatriate (and its variants) is of crucial importance. Yet there is no consensus on a single definition of, for example, a “selfinitiated expatriate” or a “migrant” (Anderson and Blinder 2015). Tharenou (2015), in a comparative review of the literatures on assigned expatriates (AEs), self-initiated expatriates (SIEs) and skilled immigrants, recently warned not to combine these conceptually distinct groups of globally mobile individuals, as doing so contaminates the results, posing a threat to the validity of our findings. In pursuit of exactness, preciseness and completeness, we find many authors who seek to define (new) types of IMEs based on an increasing number of criteria. We want to question the added value of doing so and formulate a plea for a sound theory of expatriation types.
Keywords: fi=Johtaminen ja organisaatiot|en=Management and Organization|